Juridical Review of Marriage Registration Services Using Marriage Management Information System (SIMKAH) In Makassar (Case Study of Manggala District Religious Affairs Office) - Yusril Budiman; Andi Sukmawati Assaad; Anita Marwing (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to find out how the juridical review of marriage registration services using simkah at the Office of Religious Affairs of Manggala District, Makassar City, The type of research used is qualitative, which is a form of research that aims to provide an overview of various types of data collected from the field objectively with a descriptive research type. The data collection techniques used were observation, interviews with a number of informants and documentation. The results of this research are in the background of the presence of an innovation in marriage registration services using the Marriage Management Information System or Simkah at the Manggala District Religious Affairs Office, this Simkah is a policy program issued by the government in an effort to facilitate the process of presenting marriage data in all KUA Districts in Indonesia, this Simkah has been integrated with Dukcapil, so that recording errors can be minimized, the implementation of the policy has been implemented and can be accepted by the community. However, there are several obstacles, especially the readiness of KUA human resources in Manggala District, Makassar City. In some cases, it was found that there were difficulties when using this application, the only difficulty in importing marriage data.